Modern concept of diastolic heart failure - F. T. Ageev (Кардиоваскулярная терапия и профилактика, 1970)
The paper discusses modern aspects of epidemiology, pathogenesis, clinical course, diagnostics, and treatment of the patients with chronic heart failure (CHF) and intact left ventricular ejection fraction (LVEF). CHF with intact LVEF comprises over 50% of all CHF cases, and is more prevalent in elderly women. Its leading causes include arterial hypertension (AH) and diabetes mellitus (DM). Current diagnostic problems are related to over-estimated role of LVEF reduction, which reflects substantial myocardial damage not typical for AH and DM. The limitations of classical Doppler ultrasound in diastolic dysfunction (DD) diagnostics are discussed. The combination of classical and tissue Doppler ultrasound provides a more precise estimation of systolic and diastolic LV function. This method, in combination with natriuretic peptide level measurement, is the basis for the diagnostic algorithm of CHF with intact LVEF. A new hemodynamic concept of CHF development is presented. The key clinical trials on the treatment of CHF with intact LVEF are reviewed. In conclusion, the author discusses strengths and limitations of the two concepts of CHF with intact LVEF, as a separate disease or a phenotypical manifestation (stage) of “classical” systolic CHF.